Reviews - Darcy Meeker; Greg Nolting; Jim King (Journal of Applied Communications, 1988)
Reviews of T.H.E. (Technological Horizons in Education) Journal; Surviving Corporate Transition, by William Bridges; The Media Lab, by Steward Brand; and New Directions for Agriculture and Agricultural Research: Neglected Dimensions and Emerging Alternatives, by Kenneth A. Dahlberg.